(untitled) (Desenvolvimento em Questão, 2024)
The objective of this study is to propose a methodology to analyze the profile of urban territorial development, given the lack of quantitative methodological procedures that allow verifying the living conditions of urban populations, based on the conception of urban territory. The methodology used in this investigation consisted of bibliographic and quantitative research. To estimate the index, it is necessary to compose two dimensions, Quality of Life (QOL) and Urban Structure (EU), each of which is composed of four similar variables and parameters. The results of the Urban Territorial Development Index allow monitoring of living conditions in urban areas, taking economic and social characteristics as elements.